Determinantes del rendimiento académico en Colombia: pruebas ICFES Saber 11º, 2009 (2011)
In this paper, we use the results obtained by students in math and language test ICFES Saber 11th of the second half of 2009, the aim is to identify the determinants of academic performance in Colombia. We use the Generalized Ordered Logit estimation procedure, and find a great relevance of socioeconomic variables in the performance for both areas. In particular, the income and the education level of parents have a significant positive impact on the outcome of the test. Additionally, it was found that the time in the school is statistically significant. Specifically, full-time students get better performance in the test than part-time students. This is very important in order to determine coverage education policies based on reducing the time of students in school rather than creating new institutions.